Applications and interviews: A structural analysis of two-sided simultaneous search - Ronald P. Wolthoff (Fondazione Eni Enrico Mattei (FEEM), 2011)
Much of the job search literature assumes bilateral meetings between workers and firms. This ignores the frictions that arise when meetings are actually multilateral. I analyze the magnitude of these frictions by presenting an equilibrium job search model with an endogenous number of contacts. Workers contact firms by applying to vacancies, whereas firms contact applicants by interviewing them. Sending applications and interviewing applicants are costly activities but increase the probability to match. In equilibrium, contract dispersion arises and workers spread their applications over the different contract types. Estimation of the model on the Employment Opportunities Pilot Projects data set provides values for the cost of an application, the cost of an interview, and the value of non-market time. Frictions on the worker and the firm side are estimated to each cause approximately half of the 4.7% output loss compared to a Walrasian world. I show that in the estimated equilibrium welfare is improved if unemployed workers increase their search intensity.
Keywords: J64; J31; D83; 330; Directed Search; Recruitment; Stable Matching; Labor Market Frictions; Structural Estimation; Efficiency; Policy Analysis